2015
DOI: 10.3846/btp.2015.548
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of National Intellectual Capital Measurement Models

Abstract: Abstract. National intellectual capital is regarded as an important factor of a country's ability to perform high value added func tions including the ability to create innovations. Measuring national intellectual capital is still a complicated task. In this article national intellectual capital concept and measurement models are analysed in order to show how national intellectual capital could be measured. The findings show that there are several weaknesses of measurement models validity. Those weaknesses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…0.582, stock value relative to competitors (0.544), and licenses and permits (0.472) were the most significant ones according to the respondents. The results were consistent with the results of Mačerinskienė and Aleknavičiūtė (2015) regarding the components and indices (the right to broadcast television, the right to participate in national and international competitions and events, club brand rights, advertising) identified (22). Productivity, profitability, and value in the club's indoor and outdoor environment as well as its environmental effects will lead to competitive advantage over other clubs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…0.582, stock value relative to competitors (0.544), and licenses and permits (0.472) were the most significant ones according to the respondents. The results were consistent with the results of Mačerinskienė and Aleknavičiūtė (2015) regarding the components and indices (the right to broadcast television, the right to participate in national and international competitions and events, club brand rights, advertising) identified (22). Productivity, profitability, and value in the club's indoor and outdoor environment as well as its environmental effects will lead to competitive advantage over other clubs.…”
Section: Discussionsupporting
confidence: 85%
“…In a study entitled "Intellectual capital and business performance in professional soccer societies: Evidence from a longitudinal analysis", Ricci et al (2015) concluded that the intangible assets of sports clubs (structural / communications and human capital) are effectively and positively correlated with sport performance in clubs (21). Macerinskiene and Aleknaviciuterasa (2015) found a large overlap between the assets of organizations in different countries, where these dimensions differed among the studies in four and nine aspects, depending on the environment of different communities (22). Shou and Liu (2015) concluded that intangible sport assets, due to government constraints in the country, include acquisition of social credit for Chinese sports products companies from international sports events, brand naming rights, television broadcasting rights, respect for the society, and provision of sports products through the promotion of sports stars (23).…”
Section: Introductionmentioning
confidence: 99%
“…La investigación de Mačerinskienė, I., & Aleknavičiūtė, R. (2015) "Comparative evaluation of national intellectual capital measurement models" analiza los conceptos de capital intelectual y los modelos de medición, identificando debilidades en la validez de los mismos las que se reducen con el empleo de ecuaciones estructurales para mediciones a nivel nacional y que los indicadores de medición empleados en las empresas cuentan con un elevado nivel de correlación.…”
Section: Análisis De La Literaturaunclassified
“…Intelektinio kapitalo (IK) įtaką organizacijų sėkmingai veiklai įvairiais aspektais ir lygmenimis (organizacijos, šalies, tarptautiniu) analizavo daugelis Lietuvos ir užsienio mokslininkų (Aleknavičiūtė, 2016;Mačerinskienė, Aleknavičiūtė (2015); Ramanauskaitė, 2014;Tamošiūnaitė ir kt., 2012;Atkočiūnienė, Juškaite, 2012;Stankevičienė, Liučvaitienė, 2012;Mačerinskienė, Survilaitė, 2011;Gižienė, Barkauskas, 2010;Palumickaitė, Matuzevičiūtė, 2007;Buračas, 2007;Mikulėnienė, Jucevičius, 2000;Taljūnaitė, 2010;Mikulėnienė, 2004;Znakovaitė, Pabedinskaitė, 2010;Inkinen ir kt., 2015;Hsu, Fang , 2009;Cabriata, Vaz, 2006;Gibbert, 2001;Bontis, 2000;Sullivan, 2000;Bontis,1997Bontis, , 1999Roos ir kt.1997;Brooking, 1996;Edvinsson, Malone 1997;Stewart,1997;Edvisson, Sullivan, 1996 ir kt. ).…”
Section: įVadasunclassified